2023
DOI: 10.3390/plants12030613
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Medicinal Potential of Achillea grandifolia in Greek Wild-Growing Populations: Characterization of Volatile Compounds, Anti-Inflammatory and Antioxidant Activities of Leaves and Inflorescences

Abstract: Various species of the genus Achillea L. (Asteraceae) are traditionally used worldwide for wound healing against diarrhea, flatulence, and abdominal pains, as diuretic and emmenagogue agents. In the present study, the essential oils (EOs) obtained separately from the leaves and inflorescences of wild-growing Achillea grandifolia Friv. from Mt. Menoikio and Mt. Pelion (Greece) were analyzed by Gas Chromatography–Mass Spectrometry. The major compounds found in EOs of A. grandifolia inflorescences from Mt. Menoik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, whether this is true remains to be investigated. Tsiftsoglou et al (2023) showed that cis-jasmone, present in essential oils of plants, possesses antioxidant properties [56]. The antioxidant capacities were significantly higher in the LP-L group than in the LP-H and LP-M groups, suggesting that as the Lys/Met ratio decreases, the metabolite cis-jasmone increases, improving the antioxidant capacity of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this is true remains to be investigated. Tsiftsoglou et al (2023) showed that cis-jasmone, present in essential oils of plants, possesses antioxidant properties [56]. The antioxidant capacities were significantly higher in the LP-L group than in the LP-H and LP-M groups, suggesting that as the Lys/Met ratio decreases, the metabolite cis-jasmone increases, improving the antioxidant capacity of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…is an herbaceous perennial plant, which is subendemic to the Balkan Peninsula with populations in adjacent Anatolia in Turkey. Previous studies have examined infusions of A. grandifolia with a focus on the antioxidant activity, total phenol, and total flavonoid contents of the extracts, as well as on its essential oil composition [ 9 , 10 ]. The methanol extract from A. grandifolia collected from the Balkan Peninsula is reported to have antibacterial and antioxidant properties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plants of this genus are widely used in both traditional and official medicinal practices, and they display considerable antimicrobial, antioxidant, antidiabetic, antihypertensive, sedative, anti-inflammatory, antinociceptive, cytotoxic, estrogenic and antispasmodic properties [4][5][6][7][8][9][10][11]. Certainly, one of the most famous plants from the genus Achillea is A. millefolium L., which is widely used in traditional medicine around the world and which undoubtedly has become a cosmopolitan species [12,13]. Phytochemical research has revealed that many compounds of this genus are very biologically active, and in particular, phenolics and flavonoids are the most important secondary metabolites, which have been proven to possess a wide range of pharmacological activities [14,15].…”
Section: Introductionmentioning
confidence: 99%